Exploring options for lowland rice intensification under rainfed and irrigated ecologies in East and Southern Africa: the potential application of Integrated Soil Fertility Management principles - Nhamo, N.; Kyalo, Gerald; Dinheiro, V. (Elsevier, 2014)
Increased rice production in East and Southern Africa explains the crucial role rice plays in household food and income security. However, in last three decades, rice productivity per unit area has stagnated due to abiotic and biotic factors, hence the need for the application of Integrated Soil Fertility Management (ISFM) principles. Farmyard manure, crop residues are central to improving soil fertility in rice systems. Compared to mineral fertilizer, organic manure use results in higher rice yield gains. Symbiotic biological nitrogen fixation (BNF) by grain legumes has been successfully applied to improve rice yields. However, only a few legumes are suitable for use under flooded conditions. Application of Azolla sp. improves rice yields though drought and the need for inoculum limit widespread adoption. Poor quality organic fertilizers limit their effectiveness as macronutrient sources. Where soils are P deficient, BNF and animal manure technologies seem to be of little value. In conclusion, combinations of mineral fertilizers, farmyard manure, and short seasoned legumes have the potential of improving rice yields. Further research on the application of ecology specific ISFM technologies is required in view of land degradation and climate variability. Research is needed on suitable legumes, fertilizer equivalency values of organics, fortification of organic fertilizers, and effectiveness of combinations of mineral and organic fertility inputs. We propose a step-by-step innovative approach to improving rice productivity by incorporating the components of ISFM at different stages. Decision guides essential to improved adoption and increased investment on rice production systems are required.